Transformasi Madrasah di Indonesia: Kajian Historis dan Perkembangan Kurikulum serta Kelembagaan - Debita Nafisa Sausan; Fahira Dwi Noviana; Ilham Afif; Sutrimo Purnomo (LP2M STAI Darul Kamal NW Kembang Kerang, 2026)
Madrasahs are Islamic educational institutions established to integrate religious and general education in response to societal needs. Despite extensive research, historical, curricular, and institutional dimensions are often examined separately, leaving a limited understanding of their interrelated development. This study analyzes the transformation of madrasahs in Indonesia from historical, curricular, and institutional perspectives. Using a library research approach, the study reviews books, scholarly articles, and relevant policy documents. The findings reveal that madrasahs emerged in the early twentieth century as part of Islamic educational reform and efforts to bridge the divide between religious and secular education. Their curriculum has continuously evolved in line with national education policies while preserving Islamic values and identity. Institutionally, madrasahs have transformed from community-based educational initiatives into state-recognized formal institutions under the supervision of the Ministry of Religious Affairs. Overall, the study demonstrates that madrasahs have consistently adapted to changing educational policies, social demands, and national development, enabling them to strengthen their role and sustain their relevance within Indonesia’s national education system.